2018
DOI: 10.1177/1045159518783200
|View full text |Cite
|
Sign up to set email alerts
|

“Making Up for Lost Time”: The Transition Experiences of Nontraditional Black Male Undergraduates

Abstract: This qualitative study investigated the academic and social experiences and life events that propelled 13 Black male nontraditional undergraduates to transition back to college and explored the various programs and institutional agents these men used once on campus. Findings indicated that participant’s faced challenges with college as traditional-aged students due to being under and over involved with social activities on campus or choosing to pursue a work career. As a result, participants had either delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 23 publications
(36 reference statements)
0
16
1
Order By: Relevance
“…While these assessment measures are important in a specific context, they also are quite limiting and continue to devalue how students see themselves and their own efforts. We conducted this study in the windfall of deficit narratives that continuously accost Students of Color and the negative messaging Black and Latino males receive about education as well as their efforts and abilities (see Abrica et al 2019; Brooms 2017; Goings 2018; Valencia 2010). These narratives are imposed on students throughout the educational pipeline and often limit their educational trajectories and possibilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these assessment measures are important in a specific context, they also are quite limiting and continue to devalue how students see themselves and their own efforts. We conducted this study in the windfall of deficit narratives that continuously accost Students of Color and the negative messaging Black and Latino males receive about education as well as their efforts and abilities (see Abrica et al 2019; Brooms 2017; Goings 2018; Valencia 2010). These narratives are imposed on students throughout the educational pipeline and often limit their educational trajectories and possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, as the current research discusses, students bring these assets with them into educational settings, which helps them negotiate educational terrain—some of which remains hostile to their presence and efforts, such as those identified by students in the #BlackOnCampus movement and other similar student activism on campus. 3 Extant literature on Black and Latino males’ college matriculation and efforts toward success demonstrate that these students do care about their education, rely on their communities for encouragement and sustenance, and continue to pursue success even in the face of grave challenges (Brooms 2017; Brooms et al 2018; Cerezo et al 2013; Goings 2018; Sáenz et al 2016; Wood and Palmer 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, while the literature discussed the utility of Black male initiative programs on campus, Goings (2018) found that Black male adult learners do not have access to programs that are specifically suited for their needs as adult students who have various family and work responsibilities. Thus, in many ways, Black male adult learners succeed on campus by building their own networks.…”
Section: Literature Review: Factors Of Success For Black Men In Highementioning
confidence: 99%
“…In addition to peer support, family support has been shown as a factor of success for Black male adult learners (Goings, 2016c, 2018; Rosser-Mims et al, 2014a). Goings (2016a) found that Black male adult learners succeed in college because of the sacrifices their families make for them.…”
Section: Literature Review: Factors Of Success For Black Men In Highementioning
confidence: 99%
See 1 more Smart Citation